Effect of wheat pearling process on composition and nutritional profile of flour and its bread-making performance - Navarro, José Luis (2022)
Fil: Navarro, José Luis. Universidad Nacional de Córdoba. Instituto de Ciencia y Tecnología de Alimentos Córdoba (ICYTAC); Argentina.